2018
DOI: 10.1155/2018/6459243
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Phenolic Acids and Antioxidant Activities of Different Bran Fractions from Three Pigmented Wheat Varieties

Abstract: Phenolic acid profiles and antioxidant activities of outer bran, coarse bran, and shorts from blue, black, and purple wheat were analyzed. Phenolic acids were mainly in the bound form in pigmented wheat bran fractions. Phenolic acid content decreased in the order of outer bran, coarse bran, and shorts for the three pigmented wheat varieties. HPLC analysis of phenolic extracts demonstrated that the bound form of phenolic acids contained more ferulic, isoferulic, and p-coumaric acids compared to their free count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 41 publications
3
24
0
Order By: Relevance
“…WB antioxidant activity as determined by the four in vitro methods was within the range of previous studies [ 29 , 40 ]. Ultraflo XL increased the antioxidant activity of WB hydrolysates ( Table 4 ) in consistency with previous works showing increased antioxidant activity after treatment of rice and wheat bran with different glycosidases [ 30 , 41 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…WB antioxidant activity as determined by the four in vitro methods was within the range of previous studies [ 29 , 40 ]. Ultraflo XL increased the antioxidant activity of WB hydrolysates ( Table 4 ) in consistency with previous works showing increased antioxidant activity after treatment of rice and wheat bran with different glycosidases [ 30 , 41 ].…”
Section: Discussionsupporting
confidence: 79%
“…Regarding phenolic composition, TSPC and free FA contents of WB ( Table 2 ) were in the range reported for brans from Triticum spp. (0.5-2 mg GAE/g of bran and 2.9-9.5 μg/g of bran, respectively) [ 28 , 29 ]. Most enzyme treatments used in the present study significantly increased TSPC and individual content of FA derivatives in WB ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that many of the wild edible plants have been found to be rich sources of one or more of the nutritionally important substances, such as proteins, carbohydrates, vitamins, and minerals. Besides the dietary substances, some of them also contain considerable amounts of a variety of health-promoting compounds, such as phenolic compounds [ 37 – 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Avenanthramides are naturally-derived oat phenolic compounds with very good antioxidant activity [18]. Phenolic compounds present in wheat and oat bran are insoluble, being bound to the cellulose and hemicellulose structures [19][20][21], making the conventional extraction processes very difficult. Expensive, time-consuming, and unecological procedures like chemical and enzymatic hydrolysis or mechanical crash have been applied over time as pretreatment methods for the release of the phenolic compounds from bran [16,22,23].…”
Section: Introductionmentioning
confidence: 99%